A docência no interior de Alagoas : reflexões a partir das ideias da professora Maria Mariá (1960-1963) - Silva, Hebelyanne Pimentel da (2024)
The general aim of this study was to investigate how Maria Mariá's perception of teaching work was formed, based on her involvement with the National Campaign for Free Education (CNEG). She was born in the city of União dos Palmares and studied at the Escola Normal de Maceió during the 1930s and worked as a teacher during the 1940s. Her professional life was characterized by involvement with several projects and works that marked events in the History of Education in Alagoas. From the 1950s onwards, she also expressed herself in the local and national press denouncing teachers' working conditions. The specific objectives of the study were as follows: 1) To Identify the common characteristics of the interior, specifically of the society of União dos Palmares, as Professor Maria Mariá described them; 2) To situate Maria Mariá among those who dialogued with her; 3) To verify the information contained in Maria Mariá's publications, which reveal the condition of teaching labour in the city of União dos Palmares, in connection with the results of the CNEG in Alagoas. From the point of view of the analytical framework, the work took into account two perspectives: on the one hand, the categories of place, class and gender and, on the other hand, the theoretical basis of Italian indiciary history, which articulates micro and macro analytical approaches. It was qualitative documentary research, which was operationalized through the study of imagery, written, printed, iconographic and audiovisual sources, in physical and virtual archives. The research found some unknown results about her professional life, namely: 1) Maria Mariá’s travels; 2) personal letters she exchanged with students and colleagues; 3) testimonies from former students; 4) relationships established between her and other intellectuals from Alagoas, whether Catholic or political. These facts highlight the conditioning factors in the formation of Maria Mariá's ideas in the context of the CNEG's activities. Finally, the work states that one of the characteristics of Maria Mariá's trajectory is her denunciation of the precariousness of teaching work and her commitment to a project to improve teachers' working conditions, according to a project implemented in the city of União dos Palmares. This process reveals the contradictions in which Maria Mariá is immersed, both from the point of view of her career and the constitution of the teaching profession.